Getting a little too personal? Positive and negative effects of personalized advertising on online multitaskers. (July 2022) - Kim, Jihoon (Jay); Kim, Taeyeon; Wojdynski, Bartosz W.; Jun, Hyoyeun
Highlights: Ad personalization significantly decreased Aad and Ab . Privacy concern mediated the negative impact of the personalized ad message on ad evaluation. Media tasking type did not moderate the indirect relationships between ad personalization and ad effectiveness (i.e., Aad and Ab ) through privacy concern but did moderate the direct relationship between ad personalization and ad effectiveness. Abstract: Given the increasing number of personalized ads and the prevalence of media multitasking, understanding the impact of online privacy concern on ad outcomes is important. However, the interaction effects between media multitasking and ad personalization on ad evaluation remain unexplored, including whether multitasking might lower privacy concern (i.e., cognitive performance) and improve ad evaluation and persuasion (i.e., attitudinal performance). Therefore, in the current study, we investigated the interplay between (a) level of ad personalization and (b) media multitasking and the effects of both on level of privacy concern and evaluation of the ad. We used a between-subjects experiment ( N = 219) to test the effects of non-personalized and personalized advertising on online news readers, half of whom also attended to a podcast or a movie trailer while reading. Results show that the negative effect of personalized advertising on attitude toward the ad (Aad ) and attitude toward the brand (Ab ) emerged. Participants exposed to the more personalized ad showed less favorable Aad and Ab than those exposed to the less personalized ad. Moreover, privacy concern mediated the negative impact of the personalized ad message on ad evaluation. The results also revealed that the moderated mediation effect of multitasking on personalized advertising effectiveness through privacy concern was not significant. However, media tasking type significantly moderated the direct relationships between ad personalization and ad effectiveness (i.e., Aad and Ab ). Theoretical and managerial implications are discussed.